Synthesis of New Arylmethylene Derivatives of Resorcinarene via the Catalyzed Mannich Reaction - Gawdzik, Barbara; Wzorek, Alicja; Lechowicz, Łukasz; Urbaniak, Mariusz (Synlett, 2016)
The C-arylation of Mannich base is used to obtain a series of new arylmethylene resorcinarene derivatives. Initially, aminomethyl derivative as the intermediate is formed in the Mannich reaction of resorcinarene with iminodiacetic acid. Next, activated aromatic rings act as a nucleophile in the reaction with this Mannich base and the arylmethylene derivatives of resorcinarene are prepared. The mixture of isomeric products is obtained for monosubstituted phenyl rings. Reaction with a suitably substituted phenyl ring gives one main product in good yields.
Keywords: resorcinarene; Mannich reaction; C-arylation; regioisomers; O-alkylation